Everything you need you have : how to be at home in your self - Kite, Gerad; Puddicombe, Andy (2016)
In this inspiring, revelatory book, Kite shows us how to look at things from a different perspective, and to uncover the truth: that everything we need to be happy and well, we already have inside. Drawing on the principles of ancient Chinese philosophy and his extensive experience of helping people of all ages and from all walks of life, Kite offers a route to a state of being that is authentic, expansive and liberating.
The World of Mind -- The World of Body -- The World of Home.
"Originally published in paperback in Great Britain by Short Books, London"--Title page verso.
Keywords: Contentment; Happiness; Stress management; Stress management; Contentment; Happiness. .; SELF-HELP / Personal Growth; SELF-HELP / Self-Management / Stress Management; SELF-HELP / Motivational & Inspirational; SELF-HELP / Personal Growth; SELF-HELP / Self-Management / Stress Management; Contentment; Happiness; Stress management